Seni interaktif : satu medium penyampaian dalam seni tampak - Joy, Anak Ma Wing (Universiti Malaysia Sarawak (UNIMAS), 2006)
Understanding interactive arts usually presumed to occur in two dimensions art. The effectiveness ofInteractive Art in presenting Visual Art in the installation art increased in artwork processes still less been documented. Therefore, this research are hope to solve the problems above, meanwhile to present in a form ofpersonal artwork that fulfill the needs and meaning ofthe actual Interactive Art.